Tribal Structure of the Libyan Society and its Influence on the Political Processes in the Country - Y. N. Zinin (Vestnik MGIMO-Universiteta)
The article examines the impact of tribal structure of the Libyan society to the political processes in the country in the years of Muammar Gaddafi and in the period after the victory of the Libyan opposition, expressed opinions about the possible development of events in the future. In particular, the author does not exclude the prospect of federalization of Libya.